Pathways to promote the performance of healthcare financial expenditure from an audit perspective: Evidence from Hunan Province - Shengchun Ling; Xiaoqi Tang; Qiaojun Shi (PLoS ONE, 2026)
Strengthening the audit supervision of healthcare financial expenditures and improving the performance of healthcare expenditures are critical to achieving the Healthy China strategy. This study uses data from 14 cities in Hunan Province from 2013 to 2022 and employs the DEA-Malmquist analysis method to analyze the existing problems and institutional incentives for healthcare financial expenditures in Hunan Province on the basis of estimating the performance of healthcare financial expenditures in each city. The results show that the overall performance level of healthcare financial expenditure in Hunan Province is low, and the efficiency of healthcare expenditure is trending downward. The majority of cities are in the state of increasing scale efficiency of healthcare expenditure, with insufficient scale of inputs. The main reason for the decline in efficiency is the low technological progress change index. The fundamental reasons are the shortcomings of the healthcare financial expenditure system, insufficient binding force, and inadequate supervision. Based on this, the article explores the audit mechanism of changes in expenditure performance, and then proposes specific ways for the audit to promote the improvement of healthcare financial expenditure performance, in order to give full play to the supervision and guarantee role of the audit in promoting healthcare financial expenditure performance.